β–Myosin Heavy Chain Variant Met606Val Causes Very Mild Hypertrophic Cardiomyopathy in Mice, but Exacerbates HCM Phenotypes in Mice Carrying Other HCM Mutations - Blankenburg, Robert (2014)
RATIONALE: ~40% of hypertrophic cardiomyopathy (HCM) is caused by heterozygous missense mutations in β-cardiac myosin heavy chain (βMHC). Associating disease phenotype with mutation is confounded by extensive background genetic and lifestyle/environmental differences between subjects even from the same family. OBJECTIVE: To characterize disease caused by βMHC Val606Met substitution (VM),that has been identified in several HCM families with wide variation of clinical outcomes, in mice. METHODS AND RESULTS: Unlike two mouse lines bearing the malignant myosin mutations Arg453Cys (RC/+) or Arg719Trp (RW/+), VM/+ mice with an identical inbred genetic background lacked hallmarks of HCM such as left ventricular hypertrophy, disarray of myofibers and interstitial fibrosis. Even homozygous VM/VM mice were indistinguishable from wild type animals, whereas RC/RC and RW/RW mutant mice died within 9 days after birth. However, hypertrophic effects of the VM mutation were observed both in mice treated with cyclosporine, a known stimulator of the HCM response, and compound VM/RC heterozygous mice, which developed a severe HCM phenotype. In contrast to all heterozygous mutants, both systolic and diastolic function of VM/RC hearts was severely impaired already before the onset of cardiac remodeling. CONCLUSIONS: The VM mutation per se causes very mild HCM related phenotypes, however, in combination with other HCM activators it exacerbates the HCM phenotype. Double mutant mice are suitable for assessing the severity of benign mutations.